Development of a Worldwide Consortium on Evolutionary Participatory Breeding in Quinoa - Murphy, Kevin M.; Bazile, Didier; Kellogg, Julianne; Rahmanian, Maryam (Frontiers in Plant Science, 2016)
Chenopodium quinoa is gaining global importance due to its excellent protein quality and tolerance of abiotic stresses. The last 60 years have seen major strides in the expansion of quinoa crop production and experimentation. Quinoa’s wide genetic diversity has led to its agronomic versatility and adaptation to different soil types, particularly saline soils, and environments with extremely variable conditions in terms of humidity, altitude and temperature. The potential of quinoa to contribute to global food security was recognized in the declaration of the International Year of Quinoa (IYQ, 2013). Promoting the use of improved homogeneous quinoa varieties standardized to comply with applicable norms on seeds or suited to intensified conventional agriculture farming systems may not generate the necessary resilience needed to respond to current and future global challenges. Maintaining and increasing quinoa biodiversity is imperative, as the dynamics of the global expansion of quinoa may constitute a threat to farmers if the spread is generated with a narrow genetic base. In this article, we propose that the method of evolutionary participatory breeding (EPB) could be a useful tool to develop new quinoa genetic material in cooperation with farmers. We introduce preliminary results on quinoa population development with farmers in the Pacific Northwest region of the USA. We conclude that a global collaborative network for quinoa (GCN-Quinoa) could be the baseline for participatory plant breeding programs originating in developing or developed countries to meet the needs of farmers across a diversity of agronomic systems and a wide range of physical environments.